STUDI TENTANG SPESIES LOGAM Ni DARI BEBERAPA KATALIS PREKURSOR Ni/SiO2 TERKALSINASI DENGAN TPR DAN XRD - Achmad Hanafi Setiawan (Research Center for Chemistry - LIPI, 1995)
Three different kinds of Ni-containlng species have been identified in calcined (673°K) Ni/SiO2 catalyst precursors according to their different reducibilities during temperature programmed reduction (TPR). Species A is attributed to an easily reduced species, corresponding to the bulk NiO with little interaction with the silica surface; species B is assigned to a less easily reduced form, due to small NiO particle attached to the silica surface; species C is ascribed to a very difficult to reduce species, reflecting to the strong NiO-silica surface interaction, Nickelhydrosilicate. Species A is obtained by either impregnation and ion exchanged methods, while species B and C are only produced by the ion echange method. The retained Na in the ion exchanged-NaOH catalyst affected a decreasing in the proportion of species A and a growth of the proportion of species C. The maximum value of intensity ratios of